Rhodium Nanoflowers Stabilized by a Nitrogen‐Rich PEG‐Tagged Substrate as Recyclable Catalyst for the Stereoselective Hydrosilylation of Internal Alkynes. Issue 1 (11th December 2014) - Guo, Wusheng; Pleixats, Roser; Shafir, Alexandr; Parella, Teodor
Abstract Morphology and size controllable rhodium nanoparticles stabilized by a nitrogen‐rich polyoxyethylenated derivative have been prepared by reduction of RhCl3 with NaBH4 in water at room temperature and fully characterized. The flower‐like Rh NPs are effective and recyclable catalysts for the stereoselective hydrosilylation of challenging internal alkynes and diynes, affording the (E)‐vinylsilanes in quantitative yields for a wide range of substrates. The insolubility of the nanocatalyst in diethyl ether allows its easy separation and recycling. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>